Minerals in the Foods Eaten by Mountain Gorillas (Gorilla beringei) - Cancelliere, Emma C.; DeAngelis, Nicole; Nkurunungi, John Bosco; Raubenheimer, David; Rothman, Jessica M. (PLoS ONE, 2014)
Minerals are critical to an individual’s health and fitness, and yet little is known about mineral nutrition and requirements in free-ranging primates. We estimated the mineral content of foods consumed by mountain gorillas (Gorilla beringei beringei) in the Bwindi Impenetrable National Park, Uganda. Mountain gorillas acquire the majority of their minerals from herbaceous leaves, which constitute the bulk of their diet. However, less commonly eaten foods were sometimes found to be higher in specific minerals, suggesting their potential importance. A principal component analysis demonstrated little correlation among minerals in food items, which further suggests that mountain gorillas might increase dietary diversity to obtain a full complement of minerals in their diet. Future work is needed to examine the bioavailability of minerals to mountain gorillas in order to better understand their intake in relation to estimated needs and the consequences of suboptimal mineral balance in gorilla foods.
Keywords: Minerals; Foods; Mountain Gorillas; National Park; Uganda